(untitled) (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث لدراسة تأثير 5 معدلات من السماد الآزوتي هي 0، 60، 120، 180، 240 كغ N/هـ على صفات التبكير ومحتوى البذور من الآزوت والفوسفور والبوتاسيوم. بينت الدراسة انخفاض نسبة الأزهار وتفتح الجوزات والقطفة الأولى عند المعدلات من 60 ـ 240 كغ N/هـ بالمقارنة مع الشاهد، ارتفعت بالمقابل نسبة التفرع حتى المعدل 180 كغ N/هـ وتوضع الفرع الثمري الأول وطول سلاميته الأولى، ومحتوى N عند المعدل 240 كغ N/هـ بالمقارنة مع الشاهد. لم توجد فروق معنوية في صفات التبكير عند المعدلات 60، 120، 180 كغ N/هـ وكذلك في نسبة K2O, P2O5 خلال موسمي البحث. The research was carried out to study the effect of 5 rates nitrogen fertilizer 0, 60, 120, 180, 240 kg N/ha (uria 46 %) on earliness characteristics and content seed of N, P2O5, K2O. The results showed the following: decrease in flowering percentage and opening of bolls percentage. The first harvest per rates 60 – 240 kg/ha compared with the control. On the other hand, sprouting percentage increased until rate 180 kg N/ha, higher position the first branches, the length of first nodal, and continent N also increased per rate 240 Kg N/ha. There was not significant increase of earliness characteristics, P2O5 and K2O percentage per rates 60, 120 and 180 kg N/ha during the tow seasons.